Impact of a policy of direct admission to a coronary care unit on use of thrombolytic treatment. Issue 4 (April 1989) - Burns, J M; Hogg, K J; Rae, A P; Hillis, W S; Dunn, F G
Abstract : Because thrombolytic treatment is effective only if it is given within six hours of acute myocardial infarction it is vital to admit patients to the coronary care unit as soon as possible after the acute event. A policy of admitting patients to the coronary care unit at the request of the patient's general practitioner by a telephone line that is independent of the hospital switchboard significantly reduced the delay. Those admitted via the accident and emergency department at the same hospital reached the coronary care unit 1 h 32 min after being seen by the general practitioner whereas the patients admitted directly took only 43 minutes [corrected]. The policy of direct admission also significantly increased both the percentage of patients who received thrombolytic treatment and the percentage of patients admitted within three hours from the onset of symptoms.